Analisis Ayat-Ayat Al-Qur’an tentang Jahe untuk Kesehatan dalam Perspektif Al-Quran dan Sains - Fuad, Asfal; Mugiyanto, Eko (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to analyze Quranic verses that mention ginger (Zingiber officinale), particularly in Surah Al-Insan [76:17], and to examine its benefits from both a modern scientific and Islamic spiritual perspective. The study employs a qualitative method with a descriptive-analytical approach and thematic tafsir (maudhu'i). The primary data sources include the Qur'an and tafsir literature, while secondary sources consist of scientific research on the bioactive compounds in ginger, such as gingerol, shogaol, and zingerone. The results indicate that ginger has significant health benefits, including antioxidant and anti-inflammatory effects, immune system enhancement, and prevention of degenerative diseases such as cancer and cardiovascular diseases. From a spiritual perspective, the mention of ginger in the Qur'an as a drink for the inhabitants of paradise symbolizes the balance between physical and spiritual blessings. The integration of Quranic teachings and modern science affirms that ginger is a blessed plant, reminding humans of the importance of maintaining health as an expression of gratitude to Allah SWT. This study contributes to a deeper understanding of the relationship between scientific knowledge and revelation, while encouraging the use of herbal plants to improve quality of life.